From corporate responsibility to green loyalty: How CSR initiatives shape sustainable choices among banking consumers in China - Xiao Han; Sarminah Samad; Wansoo Kim; Feiqiong Wei (Acta Psychologica)
Climate change and environmental degradation demand sustainable corporate responses. In the Chinese banking sector, CSR is increasingly recognized as a driver of green customer loyalty. This study fills a gap by employing a dual mediation-moderation model grounded in Social Identity Theory. Our model reveals that CSR directly influences loyalty (β = 0.11, p < 0.001; 32.2 % variance explained) and indirectly affects loyalty through enhanced customer communal relationships (β = 0.194, p < 0.001) and pro-environmental self-identity (β = 0.352, p < 0.001). Moreover, higher environmental knowledge amplifies these effects. The findings advance theory by demonstrating that CSR fosters a shared identity between banks and consumers, strengthening emotional bonds and driving sustainable loyalty. Practically, our results suggest that banks should integrate CSR into core operations through green financial products and adopt segmented CSR communication strategies, detailed sustainability reports for environmentally savvy customers, and educational content for others. These targeted measures can enhance customer loyalty and support the transition to sustainable banking practices.